Letter from Frederick Donnan to Georg Bredig - Donnan, F. G. (Frederick George) (1933)
Frederick Donnon (1870-1956) of University College, London thanks Georg Bredig (1868-1944) for his hospitality while visiting Karlsruhe for a German Bunsen Society for Applied Physical Chemistry meeting.
Keywords: Deutsche Bunsen-Gesellschaft für Physikalische Chemie; Donnan, F. G. (Frederick George), 1870-1956; Bredig, Georg, 1868-1944; Germany--Karlsruhe; Chemists; Chemistry--Societies, etc.